The Reward System in Secondary Schools and Teachers Productivity in Lagos State, Nigeria - Abolo, Veronica Evuarherhe (NIU Journal of Educational Research, 2024)
The need for employees in the workplace to be motivated is paramount for employees’ commitment, and higher productivity. Teachers as in loco parentis need to be well rewarded for their job to yield maximum output.  The study examined the relationship between reward system such as the use of awards, allowances and the productivity level of teachers in Lagos state secondary schools. The study employed the descriptive survey research design. The population consist the 1,737 teachers from the 41 public secondary schools in District 1, Lagos State. A multistage sampling technique was used to select 287 teachers. Three research questions and three hypotheses were raised for the study. The instrument face and content validated were done by colleagues in the field of Educational Management. A pilot study was conducted using 10 schools outside the population. The Crobach’s Alfa Co-efficient test of reliability was applied for the data where an alpha level of 0.76 was got.   The research questions were turned to hypotheses and tested using Pearson Product Moment Correlation Statistics at 0.05 Level of Significant. The findings of the study indicated that the reward system indices- rent, allowance, merit award and bonuses are related to productivity parameters of prompt completion of coursework, teachers’ class attendance and teachers meeting of timeline. Recommendations such as enforcing policy of specific reward system and publicising the various reward for teachers were given to ensure continuous teachers motivation for higher productivity in Lagos state secondary schools. Keywords: Reward system, productivity, secondary school, teachers, incentives, motivation,